Fiscal Policy and Macroeconomic Stability : Automatic Stabilizers Work, Always and Everywhere - Debrun, Xavier (IMF Working Papers; Working Paper ;, 2010)
The paper revisits the link between fiscal policy and macroeconomic stability. Two salient features of our analysis are (1) a systematic test for the government's ambivalent role as a shock absorber and a shock inducer-removing a downward bias present in existing estimates of the impact of automatic stabilizers-and (2) a broad sample of advanced and emerging market economies. Results provide strong support for the view that fiscal stabilization operates mainly through automatic stabilizers. Also, the destabilizing impact of policy changes not systematically related to the business cycle may not be as robust as suggested in the literature.